Evaluation of Ring Enhancing Lesions in the Patient Undergoing Brain CT Scan - Shah, Shashi Shekhar Prasad; Jha, Akhilesh Kumar; Akthar, Md. Kalim; Sah, Dambar; Mahato, Rajan Kumar; Chaurasiya, Chandan; Jha, Rakesh Kumar; Thakur, Amit Kumar; Adhikari, Trayush (Med Phoenix, 2023)
Introduction: Ring enhancing lesions in CT of the brain can be caused by different pathological conditions. The common lesions being some granulomas, primary brain tumors, abscess etc. CT remains essential for the investigation of ring enhancing lesions of brain.Materials and methods: A cross-sectional study was performed on a total of 60 patients undergoing brain CT scans and found to have ring enhancing lesion(s) on contrast administration. Results: The result of the study revealed that ring enhancing lesions was more common in man than women (34 out of 60 patients; 56.7%) The overall male to female ratio was 1.3:1. The age of the patients ranged from 7 to 77 years with peak incidence of lesion was found in >40 years of age comprising 28 patients (46.7%) followed by 21 to 30 age groups constituting 12 patients (20%). Single ring enhancing lesions were most common lesions comprising about 49 cases (81.67%). Neurocysticercosis (NCC) was the most common cause of ring enhancing lesions of brain comprising about 38 patients (63.3%) followed by glioblastoma multiforme (GBM) comprising about 9 patients (15%).Conclusion: CT plays an important role in the diagnosis of ring enhancing lesion and their causes. Neurocysticercosis (NCC) was the most common cause of ring enhancing lesions followed by glioblastoma multiforme (GBM).